Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kinerja Pegawai pada Yayasan Pendidikan Mulia Buana Bogor - Den Agung Trisno; Sigit Purnomo (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this study was to determine the effect of compensation and work environment om employee performance at Yayasan Pendidikan Mulia Buana Bogor Branch either partially or simultaneously. The method used is quantitative, The sampling technique used saturated sampling and obtained a sample in this study amounted to 51 responden. Data analysis using validity test, realibility test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypotesis testing. The result of this study is that compensation has a significant effect on employee performance with the regression aquation Y= 15.847 + 0,631 X1. Work environment has a significant effect on employee performance with the regression aquation Y= 6,983 + 0,833 X2. Compensation and Work Environment simultaneously have a significant effect on employee performance with the regression aquation Y= 1.930 + 0,320 X1 + 0,640 X2, a correlation value of 0.843 means that the independent variable and the dependent variable have a strong relationship level. The value of the coefficient of determination is 71,1% the remaining 28,9% is influenced by other factors. The result of the study partially show that Compensation has apositive and significant effect on Employee Performance. It can be concluded that the value of t count > t table (6,317 > 2,009), Work Environment has positif and signifikan effect on Employee Performance. It can be concluded that the value of t count > t table (9,316 > 2,009), by simultaneously showing that Compensation and Work Environment have a significant effect on Employee Performace it can be concluded that the value f count > f table or (59,144 > 2,009).